An Overview on Antifungal Drug Therapy - More, Mayuri; Jadhav, Prakash; Bhongale, Ashish; Velhal, Atish; Kumar Redasani, Vivek; Naikawadi, Nishigandha (Asian Journal of Pharmaceutical Research and Development, 2023)
Nowadays, the majority of fungal infections, including candidiasis, can cause anything from a minor mucous membrane infection to fatal systemic mycoses. Due to the most rapid increase in populations with impaired hosts, such as those with HIV/AIDS, organ transplant recipients, and chemotherapy patients, candida infections present a serious clinical challenge internationally. In addition, a dramatic rise in the number of elderly people who are vulnerable to fungal infections is anticipated in the next decades. Due to the eukaryotic structure of the cells, developing antifungal medications for these issues is more challenging than developing antibacterial medications. Therefore, there are now only a limited number of antifungal medications available to treat the wide range of fungal infections. Additionally, the antifungal arsenal against fungal diseases has been constrained by the rise in antifungal resistance and unfavourable host effects.